Research Study of Financial Literacy in Southeast Asia, Especially Indonesia and Malaysia: A Bibliometric Analysis - Drajat Stiawan; Ahmad Rosyid; Retno Wahyuningsih; Vanessa Imeldalia (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to analyze trends, scientific contributions, and collaborations in financial literacy research in Southeast Asia using bibliometric methods. A total of 635 documents from the Scopus database, published between 2009 and 2024, were analyzed through co-citation, keyword co-occurrence, and bibliographic coupling techniques using VOSviewer. The analysis identified key contributors, leading affiliations, countries, and emerging research themes in the field. Results show a significant increase in publications, particularly after 2021, peaking in 2023. Indonesia and Malaysia emerge as the leading contributors, with Universiti Malaya and Universiti Teknologi MARA being prominent institutions. Malaysian authors, particularly Sabri, MF, dominate the region’s research landscape, while Indonesia leads in overall contributions. Themes such as financial behavior, Islamic financial literacy, fintech, and financial education are prominent, reflecting the growing complexity of financial literacy in the digital age. Notably, international collaborations involving Southeast Asian researchers with counterparts in the United States, the United Kingdom, and Germany underscore the global attention this field is attracting.this study emphasizes the need for enhanced cross-country and multidisciplinary collaboration to address financial literacy disparities in southeast asia. The findings are expected to inform targeted policies, foster innovation, and strengthen regional financial education initiatives, ultimately contributing to economic stability and inclusion in Southeast Asia.